La pequena locomotora que si pudo - Piper, Watty; Hauman, George; Hauman, Doris; Ada, Alma Flor.; Bragg, Mabel Caroline, 1870- (New York : Platt & Munk, 1992)
When the other engines refuse, the Pequeña Locomotora Azul tries to pull a stranded train full of toys and good food over the mountain.
"Version original completa."
"From the Pony engine by Mabel C. Bragg"--T.p. verso.
Accelerated Reader
Keywords: Railroad trains -- Juvenile fiction; Toys -- Juvenile fiction; Juguetes -- Novela juvenil; Ferrocarriles -- Trenes -- Novela juvenil